2018
DOI: 10.1590/0104-6632.20180354s20170302
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effectiveness of Freeze-Cast Ceramic Filters Impregnated With Silver Nanoparticles

Abstract: This work aimed to produce freeze-cast pellets of porous ceramic filters of alumina and kaolinite impregnated with silver nanoparticles and to test the efficiency of bactericidal effects. Silver nanoparticles were characterized by average particle size, zeta potential and TEM. After impregnation, leached water was analyzed by graphite furnace atomic absorption spectrometry (GFAAS) that showed an efficiency of more than 99.9% in silver impregnation. From SEM/EDS, it was possible to observe that the pellets have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Sodium (Kα = 1.041 keV) also appears in the AgNP suspension. Amadio and collaborators ( Amadio et al, 2018 ) also identified sodium in this commercial AgNP suspension. According to the results of ICP-OES, the silver and zinc contents in the AgNP suspension are 130 ± 13 mg and 0.02 ± 0.01 mg per milliliter of AgNP suspension, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…Sodium (Kα = 1.041 keV) also appears in the AgNP suspension. Amadio and collaborators ( Amadio et al, 2018 ) also identified sodium in this commercial AgNP suspension. According to the results of ICP-OES, the silver and zinc contents in the AgNP suspension are 130 ± 13 mg and 0.02 ± 0.01 mg per milliliter of AgNP suspension, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…Ceramic matrix 1-100 nmCylindrical shapes -Stop bacterial growth -Highly antimicrobial-E. coli -S.aureusParticle size[78,79] …”
mentioning
confidence: 99%